2019
DOI: 10.2217/epi-2019-0277
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of tRNA-Derived Fragments and their Potential Roles in Ovarian Endometriosis

Abstract: Aim: Transfer RNA-derived fragments have been reported to play a vital role in disease progression, but their role in the pathogenesis of endometriosis remains unknown. Materials & methods: Small RNA sequencing was conducted in three paired ovarian endometriomas and eutopic endometria. The data from 22 paired samples were validated by quantitative real-time polymerase chain reaction (qPCR) and bioinformatic analysis was performed to establish the roles of these fragments in endometriosis pathogenesis. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…tRNA-derived fragments are dysregulated, which could be involved in the pathogenesis and progression of ovarian endometriosis [14]. There were significantly expressed tRNA-derived fragments in breast cancer tissues, which are hopefully to become biomarkers and valuable researches in this area [15].…”
Section: Introductionmentioning
confidence: 99%
“…tRNA-derived fragments are dysregulated, which could be involved in the pathogenesis and progression of ovarian endometriosis [14]. There were significantly expressed tRNA-derived fragments in breast cancer tissues, which are hopefully to become biomarkers and valuable researches in this area [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, of differentially expressed tRFs/tiRNAs. 86 The bioinformatic analysis of predicting downstream targets is not yet complete, which hinders the study of tsRNAs. Therefore, tsRNA research needs to overcome these limitations in order to achieve long-term development.…”
Section: Tsrnas Exist In Microvesicles and Exosomesmentioning
confidence: 99%
“…For example, in one study, qRT-PCR screened a total of 48 DE tRFs/tiRs in pancreatic cancer samples compared with adjacent normal tissue samples, including 46 upregulated tRFs/tiRs and 2 downregulated tRFs/tiRs [ 58 ]. A study investigating ovarian endometriosis [ 59 ] identified 19 upregulated and 5 downregulated tRFs, of which tiR-5s were the most common. In a study investigating high-grade serous ovarian cancer (HGSOC) [ 60 ], 2165 tRFs were found to be expressed in the sera of HGSOC patients and healthy controls.…”
Section: Trfs In Human and Animal Agingmentioning
confidence: 99%
“…High-throughput sequencing and qRT-PCR were used in one study to detect the expression of tRFs in pancreatic cancer tissues and adjacent normal tissues. In total, 48 tRFs and tiRs were identified in pancreatic cancer samples [ 59 ]. Some tRFs and tiRs were selected and verified by qRT-PCR, and the results were consistent with the sequencing results [ 59 ].…”
Section: Trfs In Age-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation